Development of Scoliosis Surgeries in Nepal: Struggles and Achievements - Bijukachhe, Binod (Grande Medical Journal, 2025)
<div class="[–thread-content-max-width:32rem] @[34rem]:[–thread-content-max-width:40rem] @[64rem]:[–thread-content-max-width:48rem] mx-auto flex max-w-(–thread-content-max-width) flex-1 text-base gap-4 md:gap-5 lg:gap-6 group/turn-messages focus-visible:outline-hidden" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="1565dc39-6bc7-41cf-b64f-cf49d736d76c" data-message-model-slug="gpt-4o"> Scoliosis treatment has advanced globally, but resource-limited countries like Nepal face ongoing challenges. Surgery began in Nepal in 2006, hindered by limited expertise, high costs, and inadequate imaging facilities. Recent progress includes surgeon training and improved outcomes, though access remains limited due to affordability. Early detection through school screenings has proven effective. While advanced technologies improve safety, their cost-effectiveness in Nepal needs evaluation. Efforts are ongoing to expand care beyond urban centers.